2020
DOI: 10.1186/s12886-020-01727-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of corneal high-order aberrations in adolescents with mild to moderate myopia

Abstract: Background This study investigated the characteristics of corneal higher-order aberrations (HOAs) of the anterior surface, posterior surface, and total cornea in adolescents with mild to moderate myopia. Methods A total of 183 patients with myopia (183 eyes) aged 8 to 18 years were enrolled in this study. The axial length (AL) of the eyes was measured by an IOL-Master, and corneal curvatures (K-values) and HOAs were measured by a Pentacam anterior segment diagnostic analyzer. Results Results of this study sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…K2 was mainly associated with spherical aberration and astigmatism before surgery, and was associated with trefoil at 30° after surgery. Zhang et al found that corneal spherical aberrations were correlated with K1 and K2 in myopia (18), which is consistent with our results. Rm is the mean radius of the curvature of the cornea.…”
Section: Discussionsupporting
confidence: 93%
“…K2 was mainly associated with spherical aberration and astigmatism before surgery, and was associated with trefoil at 30° after surgery. Zhang et al found that corneal spherical aberrations were correlated with K1 and K2 in myopia (18), which is consistent with our results. Rm is the mean radius of the curvature of the cornea.…”
Section: Discussionsupporting
confidence: 93%
“…Mohammadpour et al reported an increase in HOAs, correlating with an increase of ocular astigmatism (22). Similarly, Zhang et al found that an increase in astigmatism was associated with an increase in coma, trefoil and total HOAs (23). These ndings were similar to our results, where we found that total HOAs, coma and trefoil were at their highest levels in the astigmatism group.…”
Section: Discussionsupporting
confidence: 90%
“…Currently all the existing theoretical hypotheses that the ortho-k lens controls myopia progression, such as the retinal peripheral defocus theory ( Gardner et al, 2015 ; Smith et al, 2020 ), the aberration theory ( Hiraoka et al, 2015 ; Zhang X. et al, 2020 ; Lau et al, 2020 ), and the accommodation theory ( Batres et al, 2020 ; Song et al, 2021 ), are based on the change of the corneal shape or reduction of the refractive error after ortho-k lens wear. The biomechanical interaction between the lens and the cornea or the entire eyeball is vitally important in the course of ortho-k treatment.…”
Section: Discussionmentioning
confidence: 99%